Increase in mucormycosis hospitalizations in southeastern Brazil during the COVID-19 pandemic: a 2010-2021 time series - Ivan Lira dos Santos; Carolina Specian Sartori; André Giglio Bueno; Elisa Teixeira Mendes (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: Mucormycosis is a severe invasive fungal disease. During the coronavirus disease 2019 (COVID-19) pandemic, outbreaks have been reported worldwide, but epidemiological studies are still scarce in Brazil. Methods: We conducted a time-series cohort hospitalization study (2010-2021) in southeastern Brazil. Results: There were 311 cases (85 during the pandemic), with significant (P < 0.05) involvement of patients older than 40 years (84%), white patients (78%), rhinocerebral site (63%), and São Paulo State residents (84%). Conclusions: Mucormycosis hospitalizations were highly prevalent. Further studies are needed to assess the burden of COVID-19 on mucormycosis in Brazil.